A general degree for function triples - Väth, Martin (Topological Methods in Nonlinear Analysis, 2013)
Consider a fixed class of maps $F$ for which there is a degree theoryfor the coincidence problem $F(x)=φ(x)$ with compact $φ$.It is proved that under very natural assumptions this degree extendsto a degree for function triples which in particular provides a degreefor coincidence inclusions $F(x)\inΦ(x)$.